2021
DOI: 10.5187/jast.2021.e78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palmitoleic acid on the differentiation of bovine skeletal muscle satellite cells

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Muscle satellite cells exhibit multipotent mesenchymal stem cell activity and are capable of forming osteocytes, adipocytes, and myocytes [ 22 ]. Our previous study showed that the lipid droplet area was significantly increased and TAG accumulation was promoted in BSCs differentiated by palmitoleic acid induction [ 23 ]. Belal et al [ 24 ] showed that long-chain fatty acids (LCFAs) induced cytosolic TAG accumulation in satellite cells and significantly enhanced DGAT2 mRNA expression; however, of the two DGAT isoforms expressed in BSCs, only DGAT2 significantly responded to LCFA treatment, indicating that DGAT2 plays a critical role in TAG accumulation in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle satellite cells exhibit multipotent mesenchymal stem cell activity and are capable of forming osteocytes, adipocytes, and myocytes [ 22 ]. Our previous study showed that the lipid droplet area was significantly increased and TAG accumulation was promoted in BSCs differentiated by palmitoleic acid induction [ 23 ]. Belal et al [ 24 ] showed that long-chain fatty acids (LCFAs) induced cytosolic TAG accumulation in satellite cells and significantly enhanced DGAT2 mRNA expression; however, of the two DGAT isoforms expressed in BSCs, only DGAT2 significantly responded to LCFA treatment, indicating that DGAT2 plays a critical role in TAG accumulation in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular fat deposition is determined by both genetic and environmental factors. Intramuscular adipocytes are formed by lipid filling of fibroblasts within the muscle perimeter and consist of adipocytes distributed between muscle fibers [ 23 ]. Intramuscular adipocytes are composed mainly of phospholipids and triglycerides, the content of which is determined primarily by number and size, and provide a “marbling” site for subsequent fat deposition [ 24 ].…”
Section: Recent Research On Rumen Microbiome Contributing To Meat Qua...mentioning
confidence: 99%
“…However, in vitro studies showed the different effects of unsaturated fatty acids such as stearidonic and palmitoleic acids. While stearidonic acid inhibits adipocyte regulation by downregulating PPARγ protein, palmitoleic acid not only increased the transdifferentiation of bovine satellite cells into adipocytes by PPARγ but also upregulated PLIN1 proteins [70,71]. This is the only study to analyze the effect on PLIN1 protein expression.…”
mentioning
confidence: 95%